Radikalisme Islam dan Peradilan: Pengakomodasian Hak-Asasi Manusia dalam Proses Peradilan Komando Jihad di Indonesia - Mohammad Busjro Muqoddas; Khudzaifah Dimyati; Kelik Wardiono (Jurnal Hukum IUS QUIA IUSTUM, 2011)
The legal process from the detention to the court session for the activist of KOMJI (Jihad Commando) seems to be unprofessional, not transparent and mostly engineered by the lawgivers. The topic being examined includes how to accommodate the Human Rights aspect during the process of investigation and verdict in the case of Jihad Commando. The research using doctrinal and non-doctrinal approach is focused on the primary and secondary data. This research shows that there has been a human rights abuse in the case of Jihad Commando in all stages of the case either in the process of detention and preparing the documents bearing the case (BAP) by Kopkamtib/ Laksusda (Command for the Restoration of security and public order), Police Department, Attorney, or in the examining process in court.